Robotic assistance for skull base biopsy: a feasibility study in phantom and cadaver - Zhu, Jian-Hua; Liu, Xiao-Jing (Frontiers in Oncology, 2025)
ObjectiveBiopsy of suspicious lesions in deeply situated target areas is the first step in clinical management. This study aims to investigate the feasibility and accuracy of a novel robot system for skull base biopsy guided by Cone beam CT (CBCT).Materials and methodsThe skull phantom and cadaveric specimen were used for tests. The biopsy were performed by a custom 7 degrees of freedom robot system. CBCT images were used for planning trajectories and the data were sent to the robot control unit. Following registration, the puncture needle was automatically inserted into the target by the robot guided by navigation. Location deviation was instantly calculated and the result was verified after postoperative image scanning.ResultsAll 20 interventions were successfully performed in phantom and cadaver respectively. In phantom experiments the mean placement error was 0.56± 0.21 mm (measured by the navigation system) vs. 1.77 ± 0.13 mm (measured by image fusion) (P< 0.001); in cadaveric studies the corresponding figures were 0.71 ± 0.15 mm vs. 3.10 ± 0.18 mm (P< 0.001). Accuracy was better in the phantom experiment (P< 0.001). The Pearson Correlation Coefficients (r) was 0.639 and 0.723 in phantom experiments and cadaveric studies respectively.ConclusionThe performance of robot-assisted skull base biopsy is feasible and accurate. Clinical tests will need to be demonstrated in further studies.